AB0860 Acute phase reactant change in ankylosing spondylitis patients. (12th June 2018) - Demirer Aydemir, F.; Kenar, G.; Zengin, B.; Yarkan Tugsal, H.; Capar, S.; Birlik, M.; Onen, F.; Akkoc, N.; Can, G.
Abstract : Background: The aim of this study is to investigate the levels of acute phase reactants (APRs) in patients with ankylosing spondylitis (AS) at the time of diagnosis and during follow-up. We also evaluated the associations between APR levels and disease activity. Methods: The study included 948 patients with AS who were followed-up at Dokuz Eylul University School of Medicine Rheumatology outpatient clinic. The patients' erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels across all visits were retrospectively reviewed through the Turkbio registry and the hospital's database. Disease activity and follow-up parameters as BASDAI, ASDAS, BASFI and BASMI were taken from Turkbio visit charts. The correlation between APR and follow-up parameters were evaluated with Spearman correlation coefficient analysis. Results: There were 948 AS patients (69% male, mean age 46, 6±12, 1 years) who fulfilled the 1984 modified New York criteria. At first visit, high levels of CRP and ESR were observed in 626 (68.5%) and 578 (64.6%) patients respectively. During follow-up 84.6% of patients had high CRP and 69.5% patients had high ESR at any visit (figure 1). However in 10% of AS patients APRs did not increase at any visits. There was good correlation between ESR and CRP (r=0.666, p <0.001) . A better correlation was observed at first visit between CRP and BASDAI (r=0.81, p =0.23) or ASDAS (r=0.468, p <0.001) compared to ESR and BASDAI (r=0.111, p =0.02) or ASDAS (r=0.334, p <0.001) (table 2). Compared to BASDAI, ASDAS with either ESR (p <0.001) or CRP (very high disease activity-p <0.001, inactive disease-p=0.001) had better performance in evaluating the activity of the patient in inactive and very high levels of severe disease (table 2). Conclusions: In over 80% patients with AS had elevated levels of CRP, the most frequently used laboratory parameter, during follow-up. CRP is well correlated with ESR, and disease activity parameters as BASDAI, ASDAS, BASFI and BASMI. Compared to BASDAI; ASDAS had better agreement between activity and APRs. Interestingly, in 10% of AS patients APRs did never increase in follow-up. Disclosure of Interest: None declared